Universal Synthesis of Transition‐Metal Phosphide/Carbon Hybrid Nanosheets for Stable Sodium Ion Storage and Full‐Cell Application. Issue 18 (23rd August 2022) - Zhao, Liping; Li, Jie; Peng, Bo; Wang, Gongrui; Yu, Lai; Guo, Yiming; Shi, Liang; Zhang, Genqiang
Abstract: Transition metal phosphides (TMP), as promising candidates for sodium‐ion batteries (SIBs), have recently attracted tremendous attention by virtue of high theoretical capacity, low cost and abundant resources. Nevertheless, unsatisfactory rate performance and inferior cycling stability caused by inevitable volume expansion and sluggish charge transfer kinetics extremely restrict their practical applications. Herein, we present hierarchical TMP‐carbon hybrid structures composed of carbon coated TMP nanoparticles embedded in P and N dual‐doped porous carbon nanosheets (denoted as TMP@C⊂PNCNS, including FeP@C⊂PNCNS, CoP@C⊂PNCNS and Ni2 P@C⊂PNCNS) through a facile, extensible, one‐pot strategy followed by carbonization treatment. Thanks to the dual‐carbon protected, P and N dual‐doped and hierarchical structure, the TMP@C⊂PNCNS anodes display an extraordinary sodium‐ion storage performance. Notably, the FeP@C⊂PNCNS demonstrates a remarkable reversible capacity of 127.8 mA h g −1 after 4000 cycles at a high current density of 5.0 A g −1 with 70.8 % capacity retention. More importantly, the full‐cell based on Na3 V2 (PO4 )3 cathode and FeP@C⊂PNCNS anode delivers an outstanding energy/power density of 172.1 W h kg −1 /80.2 W kg −1 . This work provides valuable insights into the facile synthesis of hybrid nanostructures and further promotes the development of TMP‐based anode materials. Abstract : Transition metal phosphides/carbon hybrid structures (denoted as TMP@C⊂PNCNS, including FeP@C⊂PNCNS, CoP@C⊂PNCNS and Ni2 P@C⊂PNCNS) are synthesized by a facile one‐pot strategy followed by carbonization treatment, exhibiting superior sodium ion storage performance. The assembled Na3 V2 (PO4 )3 //FeP@C⊂PNCNS full‐cell delivers an exceptional energy/power density, as well as an extraordinary cycling life.